Analysis of the Needs of Junior High School Students for E-Modules Assisted by Flipbook on Pantun Writing Material - Yusma, Maili; Sinaga, Mangatur; Rahman, Elmustian (Journal of Educational Sciences, 2025)
The development of digital technology has had a significant impact on the world of education, especially in the utilization of technology-based learning media. One innovation that has emerged is the use of e-modules that can be accessed electronically and provide convenience in the learning process. At the junior high school level, Indonesian language learning materials, especially in writing pantun, are a challenge for a number of students. the development of flipbook-assisted e-modules as an alternative solution in helping students understand and apply rhyme writing techniques. This study aims to analyze the needs of junior high school students for the application of e-modules assisted by flipbooks in learning to write pantun. The method used in this research is a survey with a questionnaire instrument that aims to measure students' perceptions of e-modules. The results showed that most students had difficulty in understanding the pantun material and wanted a digital-based learning media that was more interesting and interactive. As many as 87.98% of students want the application of e-modules assisted by flipbooks as open materials that support independent learning of rhyme writing. In addition, students also expect the content of local wisdom of Malay culture, such as pacu jalur culture in the e-module.